Implementation Data Mining For Level Analysis Traffic Violation By Algorithm Association Rule - Sulaiman, Oris Krianto (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2021)
Police with regard to its function as a protector of society is expected able to take action in responding to traffic violations by conducting raid operations in uncovering violations that can be committed using analysis technique of habits how often traffic violations are committed. Detection Traffic violations that often occur simultaneously are called Association Rules.